EXPLORING THE USE OF CHATGPT IN DEVELOPING INSTRUCTIONAL MATERIALS BY SENIOR HIGH SCHOOL INDONESIAN LANGUAGE TEACHERS IN MALUKU: A MIXED-METHODS STUDY - Wa Mirna; Nursalam Nursalam; Muhamad Nasir Pariusamahu; Abd. Rahim; Jenri Ambarita (Prima Magistra: Jurnal Ilmiah Kependidikan, 2026)
The integration of artificial intelligence (AI), particularly ChatGPT, has become increasingly significant in Indonesian language instruction at the secondary school level. In the context of curriculum transformation and the demands of digital learning, teachers are required to develop adaptive, creative, and contextually relevant instructional materials. This study employed a sequential explanatory mixed-methods design. Quantitative data were collected through questionnaires distributed to senior high school Indonesian language teachers in Maluku, followed by qualitative data collection through in-depth interviews to further explain and elaborate on the quantitative findings. Data were analyzed using quantitative statistical techniques and qualitative thematic analysis to provide a comprehensive understanding of the utilization process and its implications. The findings indicate that ChatGPT has been effectively utilized as a supportive tool in developing instructional materials, including lesson plans, student worksheets, and assessment instruments. Its use contributes to increased variation and creativity in materials, improved linguistic accuracy, stronger alignment with the Merdeka Curriculum, and greater contextual relevance to students’ needs. However, teachers remain actively involved in selection, modification, validation, and contextualization to ensure academic integrity and pedagogical appropriateness. Overall, ChatGPT functions as a tool that strengthens teacher professionalism rather than replacing pedagogical roles. The findings highlight the importance of teachers’ critical and ethical engagement with AI and underscore the need for autonomous, responsible policies to guide the integration of AI into Indonesian language education.